Design of Low Noise Micro Liter Syringe Pump for Quartz Crystal Microbalance Sensor - Ridha N. Ikhsani; D.J. Djoko H. Santjojo; Setyawan P. Sakti (IAES Indonesia Section, 2018)
An injection pump was a critical aspect in the used of Quartz Crystal Microbalance (QCM) biosensor or chemical sensor in liquid. It is required that the pump should have variable speed and doesn't introduce pressure noise to the QCM sensor. In this work, the pump was developed using a micro stepper motor with a microliter syringe. The mechanical transmission transforms the rotational displacement of the motor into a translational displacement of the syringe. The flow rate of the injection pump could affect the signal pattern indicated by a signal spike or instability of the sensor resonance frequency. The developed system successfully minimized the spike signal and improved the stability of the sensor resonance by the used of the microliter syringe pump with optimizing the reaction chamber of the QCM sensor. The flow rate of the pump can be controlled with a minimum speed of 0.7 microliter per second for water. At low flow rate, there was a negligible or none of the spike signal observed during the injection and ejection of the liquid. However, at a high flow rate, few signal spikes may be observed.